Identifying and ranking the attributes of hospitals readiness to apply bring your own device: An explanatory sequential mixed study. (30th November 2022) - Jahanbakhsh, Maryam; Amini-Rarani, Mostafa; Tahmasebian, Shahram; Shahbazi, Masoumeh
Objective: The Bring Your Own Device (BYOD) approach has promoted the usage of personal mobile devices for organizational and carrier purposes. Applying a BYOD approach might provide various challenges for healthcare organizations. This study endeavored to identify the attributes of hospitals readiness in applying BYOD and to rank these attributes in order to develop appropriate policies for dealing with challenges. Materials and methods: This study is an explanatory sequential mixed method design that was carried out in two qualitative and quantitative phases for identifying the BYOD attributes and ranking them, respectively. Semi-structured interviews with 15 experts in the BYOD field were performed through in the qualitative phase. Purposive and snowball sampling approaches were used to choose experts. Thematic analysis was used to analyze qualitative data. The identified attributes were ranked in a quantitative phase by asking 10 experts using fuzzy hierarchical analysis. Results: Six main themes and 23 subthemes were identified. The findings of hierarchical analysis showed that ethical considerations, management principles, human resources, legislation considerations, cost, and technical infrastructure as the six main themes, respectively, have priority in hospitals readiness for BYOD. Conclusion: Addressing the highlighted priorities, from ethical considerations to technical infrastructure, in the formulation and implementation of formal programs and policies by health managers and authorities will prepare hospitals for the use of BYOD while decreasing the challenges associated with it.